The development of a sustainability tool - Sasaki, S (Cranfield University, 2005)
This study examines the potential for ICI Paints, a paint and coating manufacturer, to move their products towards greater sustainability. A brief review of the tools and techniques currently in use to encourage sustainable outputs is given. A new tool is proposed and developed that combines the principles from The Natural Step (TNS) and the streamlined life-cycle analysis concept. Using a matrix to contain TNS’s four system conditions, which measure sustainability in four scientific principles, against five lifecycle stages, a ‘snapshot’ of the sustainability profile of paint can be efficiently determined. Study methods included semi-structured interviews with ICI Paints employees representing different stages of the paint life-cycle. Significantly, despite being a leader in paint innovation and a Dow Jones Sustainability member, ICI Paints had performed very little life-cycle work in the past few decades. The development ofthe snapshot tool was made up ofthree areas: setting the context by understanding ICI Paints sustainability needs; meeting the sustainability needs through the development ofthe snapshot tool; finding where and how the snapshot tool could be useful to ICI Paints. By extracting common themes from interviews and secondary data, the main finding which over-arched all three objectives was the tool’s potential in communicating sustainable messages to generalist and specialist audiences. Other themes included the usefulness of the tool in sustainability focused risk management strategies. Future work includes reviewing and testing the snapshot tool in workshops.